Review on low-cost wireless communication systems for slope stability monitoring in opencast mines. (2018) - Karthik, Guntha; Jayanthu, Singam
Slope stability is one of the primary problems faced by opencast mines. The conventional geotechnical sensors are monitored by technicians in the field and the available wireless monitoring systems like slope stability radar (SSR), light detection and ranging (LiDAR) are more expensive. Critical observations on recent low-cost wireless slope monitoring systems were presented. By deploying the wireless data transmission system using advanced antennas at respective slope instruments in underground or opencast mines, we can collect data without any physical connections. Wireless sensor networks (WSNs) are well suited to monitor the movement, and it consists of sensor nodes which measure physical quantities and transmit the pre-processed measurement results to a base station. Developments in information and communications technology (ICT) support the collection, connection and analysis of data through sensing and monitoring of slopes in mines. This paper gives the detailed review on available low-cost wireless slope monitoring systems for opencast mines.